Analisis Campur Kode dalam Tuturan Komentator pada Game Ketujuh Grand Final M5 World Championship - Sabrina Tamimi; Kundharu Saddhono (Prasasti: Journal of Linguistics)
In the current era of globalization, there is a lot of competition in the field of electronic sports (e-sport). In these matches there are commentators who often combine two or more languages in one speech and elements of other languages into one speech. This study aims to determine the form of code mix in the commentator's speech in the seventh game of the M5 Global Championship match and analyze the causes of code mix. This research is descriptive qualitative in nature with data collection techniques in the form of free listening techniques. The data obtained is then analyzed using the interactive model analysis technique. The results showed that there were 95 forms of code mix. In the data, only one of the three types of code mixing was found based on the absorption element, namely outer code mixing. Meanwhile, based on the level of linguistic devices, three types were found, namely word code mixing, phrase code mixing, and clause code mixing. Factors causing code mixing are the limited use of code and the use of popular terms.